La Cantería Valenciana en la primera mitad del XV: El Maestro Antoni Dalmau y sus vinculaciones con el área mediterránea - Gómez-Ferrer Lozano, M. Mercedes (Anuario del Departamento de Historia y Teoría del Arte, 1998)
The present article through the biography of the stonemaster Antoni Dalmau, who worked in Valencia from 1440 until 1453, linked to the Cathedral, analyses the relations between the building situation in Valencia during the first half of the XVth century and other territories of Spain, especially those of the antique Corona de Aragón and the rest of the mediterranean area. It analyses also the interchange of the stone masters of these different geographical areas, as well as the multiple formation of architects and sculptors or the obligations that some official responsabilities lead to.